MISE A NIVEAU, GOUVERNANCE ET PERFROMANCE DE LA PME PRIVEE ALGERIENNE :« LE CAS DE LA PME GCP « JUTOP » : 2004 - 2014 » - SALAOUATCHI, Hichem Sofiane; SAIBI, SANDRA; ALIOUAT, BOUALEM (Journal of Human Sciences, 2017)
In a socio-economic environment characterized by very frequent mutations, the small and medium private Algerian enterprise (SME), going through a difficult experience to go to the market economy. This company will revise its management style, something already made in its competitors who practice methods of effective management and governance. Given this situation, the stakeholders in this sector are forced to upgrade their business. Our paper presents the first few items and bases on governance and small and medium enterprise and the elements offered by upgrading to apply governance in this type of business. We consolidate our research by an empirical study using a principal components analysis (PCA) factors relevant to an private Algerian SMEs located in the subsector drinks and juices, have benefited from the program upgrade based on social indicators and indicators of corporate governance. Thereafter attempt to see if the process of upgrading is capable enough to maintain the performance and growth of this SMEs.